PENGARUH MODEL PEMBELAJARAN STUDY FASILITATOR DAN EXPLAINING MENGGUNAKAN MEDIA VLOG TERHADAP PENINGKATAN KREATIFITAS DAN HASIL BELAJAR SISWA PADA MATA PELAJARAN IPS DI SMPN 11 TANGERANG SELATAN - Rahmawati, Rahmawati; Adiyati Fathu Roshanah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The Influence of Using Interactive Animation Media on the Interest in Early Reading Learning Among Second Grade Students of SD Inpres Bone, Bajeng District, Gowa Regency. This study aims to determine the effect of using interactive animation media on the interest and early reading skills of second grade students at SD Inpres Bone, Bajeng District, Gowa Regency. The type of research used is quantitative with a Pre-Experimental One Group Pretest-Posttest design. The research sample consisted of 28 second grade students selected using a saturated sampling technique. Data were collected through reading comprehension tests, reading interest questionnaires, observations, interviews, and documentation. Data analysis includes descriptive and inferential statistics using the t-test. The research results showed a significant increase in students' interest and early reading skills after using animated interactive media, with the average reading skill score increasing from 61.78 to 80.35. The t-test resulted in tcount = 10.417, which is greater than ttable = 2.228, so the hypothesis was accepted. Animated interactive media is effective in improving students' interest, motivation, and early reading skills. This media also provides a more enjoyable and interactive learning experience, so it is highly recommended for use in reading instruction in elementary schools.